PENGARUH ADAPTIVE SELLING BEHAVIOR (ASB) SEBAGAI MEDIATOR ANTARA KOMUNIKASI ORGANISASI DAN KINERJA PENJUALAN DI PT X (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
This research has a propose to examine the effect of organizational communication on sales performance through Adaptive Selling Behavior (ASB) as a mediator variable. Adaptive Selling Behavior (ASB) is a change in sales behavior through interactions with customers based on perceptual information about the nature of the sales situation. ASB helps sales staff to adopt marketing strategies and tailor their messages to suit customer needs and preferences. ASB can be used as a determinant of sales performance. One of the organizational factors that influence adaptive selling (ASB) is management style. In terms of the management style in communication, successful ASB will require understanding and collaboration between superiors and sales staff. Information in precise and accurate communication can improve sales performance. This research used a purposive sampling method of 83 sales staff participants. Based on the results of data analysis using the Hayes bootstrapping method or commonly called the PROCESS. The results showed that ASB acts as a mediator between organizational communication and performance, and produces a total effect value of p = 0.0071 (p <0.05) and can be stated as significan, and it was found that Adaptive Selling Behavior (ASB) has a role as a mediator variable in organizational communication on sales performance.